واقع التعليم والتدريب المهني والتقني في فلسطين ودوره في ريادة المشروعات الصغيرة - الدماغ، زياد جلال خليل; أبو حجير، طارق مفلح Abu Hujair, Tareq Mufleh (المنظمة العربية للتنمية الإدارية, 2022)
يهدف البحث إلى دراسة واقع التعليم والتدريب المهني والتقني في فلسطين ودوره في ريادة المشروعات الصغيرة، الأمر الذي يساهم في تحقيق التنمية المستدامة، وقد استخدم الباحثان المنهج الوصفي التحليلي في إجراء الدراسة، وتم تطبيق الاستبانة كأداة لجمع المعلومات على عينة عشوائية مكونة من (180) مفردة موزعة على أصحاب المشروعات الصغيرة، وقد توصل الباحثان إلى العديد من النتائج حسب آراء مجتمع الدراسة أهمها: 1-تبين وجود موافقة متوسطة حول واقع مستوى التعليم والتدريب المهني والتقني. 2-يوجد تأييد بدرجة متوسطة لمستوي ريادة المشاريع الصغيرة. 3-هناك تأثير إيجابي لمحاور واقع التعليم والتدريب المهني والتقني بكافة أبعاده في ريادة المشاريع الصغيرة. وفي ضوء نتائج الدراسة أوصى الباحثان جميع الجهات القائمة على برامج التعليم والتدريب المهني والتقني بالعمل على ما يلي: 1-ضرورة تقويم البرامج والمناهج بشكل دوري ومواكبة التطورات العالمية. 2-العمل على استقطاب مدرسين من ذوي الكفاءة والخبرة. 3-تهيئة وتطوير البنية التحتية للبرامج المهنية والتقنية. 4-دعم خريجي البرامج المهنية والتقنية بتوفير فرص عمل لهم. This research aims at studying the reality of vocational and technical education and training in Palestine, and its role to the entrepreneurship of small enterprises, which contributes to achieve a sustainable development. The researchers used a descriptive analytical method in conducting the study, while a questionnaire was applied to collect data from a random sample consisted of 180 individuals, representing owners of small projects. The researchers reached a number of results, the most important of which are: 1- There is a moderate agreement on TVET reality level. 2- There is a medium support for small entrepreneurship. 3- All dimensions of TVET current reality have a positive impact on small entrepreneurship. In the light of study results, The researchers recommended that all providers of TVET programs should work on the following: 1- The necessity to evaluate programs and curricula periodically, while keeping pace with global developments. 2- Attracting qualified and experienced instructors. 3- Developing the professional and technical programs infrastructure. 4- Supporting graduates of professional and technical programs by providing them job opportunities.
Keywords: ريادة الأعمال -- المشاريع الصغيرة -- التنمية المهنية -- المؤسسات التعليمية -- فلسطين